Enrollment of special education students in a Brazilian public university - Kele Cristina da Silva; Sandra Martins Eli Sartoreto de Oliveira; Lúcia Pereira Leite (Arizona State University, 2018)
The significant increase of the enrollment rate of target-public students from Special Education to Higher Education has been problematized today. This text aims to describe and analyze the contributions of using of an instrument provided by INEP/MEC to identify this public in a university context. Sample used in this research was compounded by 597 students who declared themselves as people with disabilities, pervasive developmental disorders or intellectual giftedness according a mapping done by a São Paulo State public university in Brazil. Data collection was done through an electronic formulary during the re-enrolling process, according the Higher Education Census. Although the findings of this study revealed that the collection instrument indicated by INEP/MEC allowed mapping data of the special education public in this teaching modality, it was found that the use of terminologies, without making explicit the target-audience features, corroborated an overvaluation of the disability indication by the respondents. In spite of these findings, this kind of study asserts the provision of public policies to this purpose has helped to demystify the anonymity of persons with disabilities in higher education.